2009 10th International Symposium on Quality of Electronic Design 2009
DOI: 10.1109/isqed.2009.4810287
|View full text |Cite
|
Sign up to set email alerts
|

New subthreshold concepts in 65nm CMOS technology

Abstract: In this paper challenges observed in 65nm technology for circuits utilizing subthreshold region operation are presented. Different circuits are analyzed and simulated for ultra low supply voltages to find the best topology for subthreshold operation. To support the theoretical discussions different topologies are analyzed and simulated. Various aspects of flip-flop circuits are described in detail to study which topology would be most suitable for ultra low supply voltage and low-power applications. Simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…As it can be seen in Fig.3, in write cycle, when write=1, DATA=1, and WWL=0 (RDWL=0), node x is charged to VDD through three stacked PMOS transistors. As it is shown in [3], the three stacked PMOS has a much higher speed of three stacked NMOS transistors. So, in this case, write and read cycle are sperated and they are done, in two different modes due to WWL and RDWL signals.…”
Section: Sram Cellmentioning
confidence: 90%
See 1 more Smart Citation
“…As it can be seen in Fig.3, in write cycle, when write=1, DATA=1, and WWL=0 (RDWL=0), node x is charged to VDD through three stacked PMOS transistors. As it is shown in [3], the three stacked PMOS has a much higher speed of three stacked NMOS transistors. So, in this case, write and read cycle are sperated and they are done, in two different modes due to WWL and RDWL signals.…”
Section: Sram Cellmentioning
confidence: 90%
“…But for lower supply voltage or for sub-threhold design, M7-M10 should be upsized too much. In [3] it's shown that for lower supply voltages, PMOS transistors are faster than NMOS's. So, in this case, it's shown that if we use the PMOS transistors to implement the write path, the write cycle is improved.…”
Section: Sram Cellmentioning
confidence: 99%
“…The second problem in stacking is the reduction in current due to stacked devices which results in loss of speed in subthreshold region. This, however, can be offset by body biasing [7]. For example, in [7] authors proposed complementary hybrid latch flip-flop (CHLFF) for ultralowpower applications and Forward Body Bias (FBB) was used to increase the speed of the PMOS (p-channel MOSFET) stacked network.…”
Section: Challenge 1: Pvt Variationmentioning
confidence: 99%
“…This, however, can be offset by body biasing [7]. For example, in [7] authors proposed complementary hybrid latch flip-flop (CHLFF) for ultralowpower applications and Forward Body Bias (FBB) was used to increase the speed of the PMOS (p-channel MOSFET) stacked network. It was found that reducing the supply voltage to 0.3 V in an NMOS (n-channel MOSFET) stacked flip-flop (FF) causes some failures in corners.…”
Section: Challenge 1: Pvt Variationmentioning
confidence: 99%
“…For example, in the super-threshold region PMOS is usually sized twice as big as NMOS to achieve equal PMOS and NMOS current or rise and fall delay. But it has been found that in the near/sub-threshold region PMOS needs to be upsized heavily compared to NMOS in order to achieve equal rise and fall delay [8][9] [10]. This is because the current becomes exponentially related to the threshold voltage when VDD approaches the threshold voltage.…”
Section: Introductionmentioning
confidence: 99%